Grain Size Effect on LCF Behavior of Two Different FCC Metals. (2016) - Mahato, J.K.; De, P.S.; Sarkar, A.; Kundu, A.; Chakraborti, P.C.
Abstract: Low cycle fatigue behavior of single phase polycrystalline aluminium and copper has been investigated under completely reversed strain-control condition. In both cases two different grain sizes have been considered. It is found that over the range of strain amplitude of 0.20 to 1.0 pct the cyclic life is low in case of coarse grained aluminium as compared to fine grained condition. However, the cyclic stress response of coarse grained aluminium is completely different from that of fine grained condition. In contrast to fine grained aluminium cyclic hardening of coarse grained aluminium is found to occur in different stages for all strain amplitudes. The initial hardening is first stabilized and then increases by substantial amount. On the other hand, although the nature of variation of cyclic stress response with number of cycles is almost similar for both fine and coarse grained copper, the magnitude of hardening all through the cyclic life is more in case of coarse grained copper. This is attributed to higher twin density in case of coarse grained copper. However, the cyclic life in coarse grained copper is less as compared to fine grained copper. Irrespective of cyclic hardening behavior and stacking fault energy it is found that cyclic life is more in case of fine grained materials.